Systemic research in individual, couple, and family therapy and counseling - Ochs, Matthias; Borcsa, Maria; Schweitzer, Jochen (Springer International Publishing, 2020)
Chapter 1.The Heidelberg Systemic Research Conferences: Its History, Goals and Outcomes -- Section 1: Innovations in Systemic Research Paradigms -- Chapter 2. Contributions of Systemic Research to the Development of Psychotherapy -- Chapter 3. The Social Present in Psychotherapy: Duration of Nowness in Therapeutic Interaction -- Chapter 4. Significant Moments in a Couple Therapy Session: Towards the Integration of Different Modalities of Analysis -- Chapter 5. Collaborative Family Program Development: Research Methods that Investigate and Foster Resilience and Engagement in Marginalized Communities -- Chapter 6. Resilience of Individuals, Families, Communities and Environments: Mutually Dependent Protective Processes and Complex Systems -- Section 2: Methodological Considerations -- Chapter 7. Relational Research (Trans)forming Practices -- Chapter 8. Discourse Analysis and Systemic Family Therapy Research: The Methodological Contribution of Discursive Psychology -- Chapter 9. From Research on Dialogical Practice to Dialogical Research: Open Dialogue is Based on A Continuous Scientific Analysis -- Chapter 10. Systemic Practitioner Research: Some (Epistemological) Considerations and Examples -- Chapter 11. Family Secrecy – A Challenge for Researchers -- Section 3: Answering Clinical Issues Using Scientific Knowledge and Methods -- Chapter 12. Mentalization in Systemic Therapy and its Empirical Evidence -- Chapter 13. Mindfulness and Compassion-Based Interventions in Relational Contexts -- Chapter 14. What are the Emotions? How Emotion-Focused Therapy Could Inspire Systemic Practice -- Chapter 15. From Reactivity to Relational Empowerment in Couple Therapy: Insights from Interpersonal Neurobiology -- Chapter 16. Relationship Distress: Empirical Evidence for a Relational Needs Perspective -- Chapter 17. Violence in Families: Systemic Practice and Research -- Section 4: Improving Therapy Quality by Feedback.– Training and Publication -- Chapter 18. Research Informed Practice of Systemic Therapy -- Chapter 19. The Effectiveness of Three Psychotherapies of Different Type and Length in the Treatment of Patients Suffering from Anxiety Disorders -- Chapter 20. The SCORE in Europe: Measuring Effectiveness and Assisting Therapy -- Chapter 21. The Idiographic Voice in a Nomothetic World: Why Client Feedback is Essential to Our Professional Knowledge -- Chapter 22. Therapeutic-Factor-Oriented Skill-Building in Systemic Counselling: Productively Conjoining Attitude and Method -- Chapter 23. Publication in Family Therapy Journals: Family Process, Journal of Family Therapy and Australian and New Zealand Journal of Family Therapy – A Discussion with Editors. .
Keywords: Familientherapie